2015
DOI: 10.1002/jemt.22468
|View full text |Cite
|
Sign up to set email alerts
|

Do the monomers release from the composite resins after artificial aging?

Abstract: It was observed that use of additional polymerization processes might have positive effect on the decrease of residual monomer. In the light of the results, we suggest that indirect composite resins have more outstanding features than direct composite resins in terms of biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Thus, our aim was to reach LLOQs as low as possible and consequently sufficient sensitivity. In this sense, for BisEMA, BisGMA, BPA, CQ, HEMA, TEGDMA, and UDMA, the LLOQs reached using our method are lower or similar to the ones reported in literature . To the best of our knowledge, no data on the LLOQs for the other target compounds was available for comparison.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, our aim was to reach LLOQs as low as possible and consequently sufficient sensitivity. In this sense, for BisEMA, BisGMA, BPA, CQ, HEMA, TEGDMA, and UDMA, the LLOQs reached using our method are lower or similar to the ones reported in literature . To the best of our knowledge, no data on the LLOQs for the other target compounds was available for comparison.…”
Section: Resultssupporting
confidence: 71%
“…Extraction solvents typically used are as follows: (1) water or aqueous mixtures, such as cell culture media, saliva, or buffer solutions, to simulate clinical relevant conditions; and (2) organic solvents, usually ethanol‐ or methanol‐based, to simulate worst‐case scenarios . Nowadays, the elution of the different compounds from dental materials tends to be analyzed more and more by liquid chromatographic methods, such as HPLC and LC–MS/MS . Nevertheless, researchers in the dentistry field tend to stay vague about details on the used analytical parameters and often proper method validation is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, anticipating and managing changes in this temperature can be quite complex as the extent of temperature variation is affected by several factors, including the type of light-curing unit (LCU) used, power density, exposure duration, distance between pulp and restorative materials, etc. 3,4,5 Nevertheless, the heat produced by different dental procedures and/or materials used is undoubtedly one of the biggest sources of stress that can affect the vitality of Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. the pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Tabatabaei et al 40) and Tokay et al 41) found that the thermocycling increased the amount of monomer released in significant amounts. These findings are in parallel with the results of our study.…”
Section: Discussionmentioning
confidence: 99%